Scams in land transactions: a review of the decision in public bank bhd. V T Sivam Tharamalingam [2017] - Sufian, Azlinor (2017)
Nowadays it is quite rampant that consumers are being the subject of scams; both either in relation to goods or services. Buyers of land (or potential buyers) are also without exception, become the subject of scams. Inexperienced buyers who probably may be the first-time buyers or young buyers seemed to be vulnerable and easily been influenced by scammers. The advertisements for the sale of land through the social media, (which is now very common) or through other means are normally very promising. Thus, it easily attracts inexperienced buyers to make their commitments. Apart from that there were situations where the registered proprietors lost their title to the fraudster. It is the objective of this paper to present a case review on one of the latest cases decided by the Court of Appeal involving fraud in land transaction. This paper will suggest several steps on how the scams in land transactions may be avoided and the remedies available under the law. It will involve the functions and roles that should be played by various parties in combating the scams in land transactions.